Dabigatran vs. warfarin in relation to the presence of left ventricular hypertrophy in patients with atrial fibrillation: the Randomized Evaluation of Long-term anticoagulation therapY (RE-LY) study - Verdecchia, Paolo; Brückmann, Martina (Europace, 2018)
AbstractAim. We tested the hypothesis that left ventricular hypertrophy (LVH) interferes with the antithrombotic effects of dabigatran and warfarin in patients
Gesehen am 05.05.2020
Online publish-ahead-of-print 17 May 2017